Analysis of Work Culture and SWOT on Employee Performance at the Language School of the National Police Education and Training Institution - Rahayu, Yuni Puji; Zaharuddin, Zaharuddin; Taufik , Kemal (Journal of Social Science and Education Research, 2024)
Three important aspects that influence performance and effectiveness at Sebasa Lemdiklat Polri are as follows: work culture analysis, SWOT analysis, and employee quality. The research objectives are as follows: To analyze work culture, analyze SWOT in realizing the quality of effective and efficient employee performance and to analyze what factors influence the quality of employee performance at the National Police Education and Training Language School of the Republic of Indonesia. The research used in this research uses interpretive qualitative research methods with a single case study research strategy. This research explores the work culture at Sebasa Lemdiklat Polri, which includes the values, norms and practices implemented in the organization. SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) is used to identify the strengths, weaknesses, opportunities and threats faced by Sebasa Lemdiklat POLRI. The results of this analysis provide a comprehensive picture of the organization's strategic position, and help in better planning and decision making. This research analyzes factors that influence employee quality, such as training, motivation, and work environment. A strong work culture, comprehensive SWOT analysis, and improving the quality of employees are key factors in achieving the organizational goals of Sebasa Lemdiklat Polri. It is hoped that the recommendations resulting from this research will help Sebasa Lemdiklat Polri in developing effective strategies to improve performance and achieve long-term success.